Adsorption of Metoclopromide Hydrochloride onto Burned Initiated Iraqi Bentonite - Alkhazrajy, Omar S; Abdul Latif, Mohammed H; Al – Abayaji, Maha A (Al-Nahrain Journal of Science, 2012)
Bentonite is widely used as an adsorbent for the management of patients with drug overdoses, poisonings and environment treatment. Multiple oral doses of bentonite increase the elimination of several, but not all, drugs and poisons. Adsorption of Metoclopromide hydrochloride onto initiated burned bentonite from aqueous solution has been investigated, an adsorption isotherms and FTIR spectroscopy characterization were studied. From the adsorption studies may be deduced that amount of Metoclopromide hydrochloride adsorbed by initiated burned bentonite slightly increases with the decrease in the pH of the solution and the increase in solution temperature caused a simple increase in the adsorption capacity values found from Freundlich model (R2=0.975). Thermodynamic functions, the change of free energy (ΔG= -7.924 K J mol-1), enthalpy (ΔH=9.612 J mol-1) and entropy (ΔS=2.498 J mol-1k-1) of sorption were also calculated. These parameters show that the sorption process is spontaneous and endothermic at 37 ◦C. The effect of contact time, clay dosage and ionic strength also studied.